Challenges and Opportunities for School-Based Teacher Training in Zanzibar - Alawi, Saleh Mussa (Journal of Social Sciences and Management Studies, 2024)
This research delves into the Challenges and Opportunities for School-Based Teacher Training in Zanzibar, employing a comprehensive mixed-methods approach. The study engages both quantitative and qualitative methodologies, incorporating questionnaires and interviews to gather insights from 110 participants. The sample comprises teachers actively participating in the program, head teachers, and program facilitators, selected through random and purposive sampling methods. Utilizing interviews for head teachers and facilitators, and questionnaires for teachers, the data collection process was meticulous. The quantitative data underwent analysis through statistical software, while qualitative analysis deciphered insights from the interviews. The results underscore overwhelmingly positive perceptions regarding the program's impact, as 95.6% of respondents expressed strong support. Significantly, 51.1% highlighted the imperative to prioritize teaching methodology and assessment methods, while 45.5% advocated for the integration of ICT into teaching practices. However, the research also unveiled challenges faced by the program, including financial constraints, inadequate teaching aids and equipment, and deficiencies in facilitator skills. The study puts forth actionable recommendations, emphasizing the necessity for needs-based training programs, continuous development for facilitators, and augmented budget allocation for materials, technology, and participant allowances. These improvements aim to fortify the efficacy and sustainability of school-based teacher training programs in Zanzibar.